2014
DOI: 10.1177/070674371405900306
|View full text |Cite
|
Sign up to set email alerts
|

The Mistreatment of Major Depressive Disorder

Abstract: Objective: To examine the effects of classification on treatment in major depressive disorder (MDD).Method: This is a narrative review.Results: MDD is a highly heterogeneous category, leading to problems in classification and in specificity of treatment. Current models classify all depressions within a single category. However, the construct of MDD obscures important differences between severe disorders that require pharmacotherapy, and mild-to-moderate disorders that can respond to psychotherapy or remit spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Not all research teams have reported significant WM abnormalities in MDD patients however [ 121 , 135 ]. The reasons for such discrepant results are not entirely clear, but differences in technique and evidence that depression is an aetiologically heterogeneous syndrome rather than a single discrete neurobiological entity [ 136 ] is likely also relevant.…”
Section: Neuroimaging Abnormalities In Mddmentioning
confidence: 99%
“…Not all research teams have reported significant WM abnormalities in MDD patients however [ 121 , 135 ]. The reasons for such discrepant results are not entirely clear, but differences in technique and evidence that depression is an aetiologically heterogeneous syndrome rather than a single discrete neurobiological entity [ 136 ] is likely also relevant.…”
Section: Neuroimaging Abnormalities In Mddmentioning
confidence: 99%
“…Mood disorders are the second most frequent group of mental disorders in Europe, and these mood disorders are dominated by MDD, affecting 7% of the population [2]. MDD patients experience loss of self-esteem, disturbed sleep, grumpiness, increased fatigue, reduced pleasure and concentration [4]. Depression is a very important risk factor of suicide [5].…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) can cause significant distress and impairment in individuals, and it also places a substantial burden on society 2. Despite available treatments, MDD is a remarkably heterogeneous disorder, causing problems in classification and treatment specificity 3. Studies have consistently reported that personality traits predict4 and influence the treatment outcome of depression in both pharmacotherapy5 and psychotherapy 6.…”
Section: Introductionmentioning
confidence: 99%